Integrating Multiple Control Actions in Advanced Microgrids: an Analogy to Well-Established Inverter Control - João M. S. Callegari; Lucas S. Araujo; Dener A. de L. Brandão; Braz J. Cardoso Filho; Danilo I. Brandão (Eletrônica de Potência)
This paper proposes multiple control actions applied to centralized advanced microgrids (MGs). The well-established control actions feedback (FB), feedforward (FF), and disturbance decoupling (D) commonly used in current control of distributed energy resources (DERs) are herein extended to advanced MGs. Analytical expressions are derived to show the effect of each control action on the well-established DER current control and then on advanced MG control. Comprehensive comparisons between the feedback and all control action strategies are performed for both DER and MG controls. Simulation and experimental results show a dynamic response improvement in load disturbance rejection when all control actions are considered, as well as a reduction in steady-state error for the grid power flow control. By employing low-bandwidth communication between DERs and central controller, no hardware retrofit is required in comparison to what is needed in other state-of-the-art centralized MG controls.